A Comparative Investigation of the Effect of Microstructure and Crystallographic Data on Stress-Oriented Hydrogen Induced Cracking Susceptibility of API 5L X70 Pipeline Steel - Mohammad Ali Mohtadi-Bonab; Edwan Anderson Ariza-Echeverri; Mohammad Masoumi (Metals, 2022)
In this research, stress-oriented hydrogen induced cracking (SOHIC) test was carried out on a 50 mm thickness of a commercial API 5L X70 steel plate. The evolution of microscopic features such as phase, boundary, interface, grain, and crystallographic data was analyzed before and after SOHIC, in order to comprehend the effect of crystallographic orientation on SOHIC propagation. Chemical composition and previous thermomechanical processing even finish rolling temperature and cooling rate determine the ferrite matrix microstructure. A recrystallized ultrafine ferrite grain with about 3–5% degenerated pearlite dispersed in the microstructure was characterized, called as-received specimen. The average lattice strain and dislocation density was calculated first using multiple Gaussian peak-fitting method from XRD pattern. Electrochemically charged combination mixed H2S-CO2 solution, constant hydrogen injection, and external loading were applied to tensile specimen, in order to simulate the H2S and CO2 environment. The results show that local misorientation and Taylor factor analyses predicted the possibility of hydrogen crack nucleation especially at boundaries and interfaces. Moreover, SOHIC crack propagation occurred along the mid-thickness of the cross section of steel plate along the ferritic boundaries, pearlitic colonies, and ferrite-cementite interfaces. Moreover, the crack propagated along distorted {110} and {001} grains, indicating a strong strain gradient towards the boundaries. The analysis of XRD patterns of SOHIC tested specimen by multiple Gaussian peak-fitting method estimated about 68% increment in micro-deformation and approximately 170% increase in dislocation density.